Portable Ultrasound Device Usage and Learning Outcomes Among Internal Medicine Trainees: A Parallel‐Group Randomized Trial. Issue 3 (19th February 2020) - Kumar, Andre; Weng, Yingjie; Bentley, Jason; Almli, Marta; Hom, Jason; Witteles, Ronald; Ahuja, Neera; Kugler, John
Abstract : BACKGROUND: Little is known about how to effectively train residents with point‐of‐care ultrasonography (POCUS) despite increasing usage. OBJECTIVE: This study aimed to assess whether handheld ultrasound devices (HUDs), alongside a year‐long lecture series, improved trainee image interpretation skills with POCUS. METHODS: Internal medicine intern physicians (N = 149) at a single academic institution from 2016 to 2018 participated in the study. The 2017 interns (n = 47) were randomized 1:1 to receive personal HUDs (n = 24) for patient care vs no‐HUDs (n = 23). All 2017 interns received a repeated lecture series regarding cardiac, thoracic, and abdominal POCUS. Interns were assessed on their ability to interpret POCUS images of normal/abnormal findings. The primary outcome was the difference in end‐of‐the‐year assessment scores between interns randomized to receive HUDs vs not. Secondary outcomes included trainee scores after repeating lectures and confidence with POCUS. Intern scores were also compared with historical (2016, N = 50) and contemporaneous (2018, N = 52) controls who received no lectures. RESULTS: Interns randomized to HUDs did not have significantly higher image interpretation scores (median HUD score: 0.84 vs no‐HUD score: 0.84; P = .86). However, HUD interns felt more confident in their abilities. The 2017 cohort had higher scores (median 0.84), compared with the 2016 historical control (median 0.71; P = .001) and 2018 contemporaneous control (median 0.48; P < .001). Assessment scores improved after first‐time exposure to the lecture series, while repeated lectures did not improve scores. CONCLUSIONS: Despite feeling more confident, personalized HUDs did not improve interns' POCUS‐related knowledge or interpretive ability. Repeated lecture exposure without further opportunities for deliberate practice may not be beneficial for mastering POCUS. Abstract :